Analysis of Financial Performance after and Before Debt Restructuring In Mining Sector on the IDX (Indonesia Stock Exchange) - Sibarani, Steven Arrow Rinel; Yuniningsih, Yuniningsih (International Journal of Scientific Research and Management (IJSRM), 2023)
Debt restructuring is an action that has often been used, especially in one of the largest industries in Indonesia, namely mining, to assist companies in resolving problems from their obligations. The exploration and expansion in mining industries require big capital. Raising capital through debt is one of the ways to raise capital other than listing a company through an Initial Public Offering. On the company's financial performance, debt restructuring is likely to have a beneficial impact. Purposive sampling was used to gather the sample for this study, which included 13 mining companies registered on the IDX that underwent debt restructuring between the years of 2015 and 2018. The research was conducted by comparing the company's financial performance 3 years before and after debt restructuring through the calculation of financial ratio analysis: Current Ratio (CR), Debt Ratio (DR), Return on Assets (ROA), Total Assets Turnover (TATO), Time Interest Earned Ratio (TIER), and Economic Value Added (EVA) through the Paired Sample T-Test, and Wilcoxon Signed Rank Test in IBM SPSS Statistics 25 application to see the difference on every ratio that is tested. This study found a difference in financial performance in the ROA and TIER ratios, while there was no difference in the CR, DR, TATO, and EVA ratios.